ASSESSMENT OF ECONOMIC LEAKAGE IN TOURISM SYSTEM OF THE SUNDARBANS (BANGLADESH) - Kamrul HASSAN; Oaisharia Vocto OISHI; Farzana AFROZ (Analele Universităţii din Oradea: Seria Geografie)
The tourism industry employs the term ‘economic leakage’ to describe the phenomenon of tourism revenue of a destination leaving to outside economy from the destination of reference. This study aims to measure the economic leakage in the tourism system of the Sundarbans in Bangladesh. To address the research aim, a quantitative research methodology has been employed. A total of 22 participants were interviewed out of 190 tourism businesses offering tours in the Sundarbans. This research has found that 28% of economic leakage occurred in the tourism system of the Sundarbans. Imported products (e.g. food and beverage, fuel), imported services (e.g. advertising, foreign payments), and other issues (e.g. outside employee salaries, training and seminars, forest fees, government taxes) have been identified as contributing factors to economic leakage. Measuring the quantity and identification of the contributing factors of economic leakage can help policymakers to maximize the economic benefits of a destination by sourcing tourism products and services locally.